Altered Processing and Integration of Multisensory Bodily Representations and Signals in Eating Disorders: A Possible Path Toward the Understanding of Their Underlying Causes - Riva, Giuseppe; Dakanalis, Antonios (Frontiers in Human Neuroscience, 2018)
According to the Diagnostic and Statistical Manual of Mental Disorders (DSM V) eating problems are the clinical core of eating disorders (EDs). However, the importance of shape and weight overvaluation symptoms in these disorders underlines the critical role of the experience of the body in the aetiology of EDs. This paper suggests that the transdiagnostic centrality of these symptoms in individuals with eating disorders may reflect a deficit in the processing and integration of multisensory bodily representations and signals. Multisensory body integration is a critical cognitive and perceptual process, allowing the individual to protect and extend her/his boundaries at both the homeostatic and psychological levels. To achieve this goal the brain integrates sensory data arriving from real-time multiple sensory modalities and internal bodily information with predictions made using the stored information about the body from conceptual, perceptual, and episodic memory. In this view the emotional, visual, tactile, proprioceptive, and interoceptive deficits reported by many authors in individuals with eating disorders may reflect a broader impairment in multisensory body integration that affects the individual’s abilities (a) to identify the relevant interoceptive signals that predict potential pleasant (or aversive) consequences and; (b) to modify/correct the autobiographical allocentric (observer view) memories of body related events (self-objectified memories). Based on this view, the paper also proposes a strategy, based on new technologies (i.e., virtual reality, neuro/biofeedback and brain/body stimulation), for using crossmodal associations to reactivate and correct the multisensory body integration processes.